2021
DOI: 10.1186/s12913-021-06465-6
|View full text |Cite
|
Sign up to set email alerts
|

The combination of psychosocial working conditions, occupational balance and sociodemographic characteristics and their associations with no or negligible stress symptoms among Swedish occupational therapists – a cross-sectional study

Abstract: Background The numbers of people who are on sick leave due to mental health problems, such as exhaustion disorder, are increasing in Sweden. One of the most affected groups is healthcare professionals. In order to develop preventive strategies to promote a sustainable working life for occupational therapists, there is a need to understand the associations between psychosocial working conditions, occupational balance and no or negligible stress symptoms. To the best of our knowledge, neither the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(43 reference statements)
0
6
0
1
Order By: Relevance
“…Проте проведення масових епідеміологічних досліджень в Україні пов'язані з низкою труднощів. Запропонована деякими авторами [3][4] оцінка впливу в динаміці виробничих чинників по санітарно-гігієнічним характеристикам умов праці часто є неможливою через часті та різноманітні перебудови виробництв, ліквідацію чи зміну форми власності, плинність кадрів тощо. Оцінка здоров'я досліджуваних когорт за результатами періодичних медичних оглядів і, особливо, за рівнем захворюваності з тимчасовою втратою працездатності [5][6] також є далекою від об'єктивної.…”
Section: вступunclassified
“…Проте проведення масових епідеміологічних досліджень в Україні пов'язані з низкою труднощів. Запропонована деякими авторами [3][4] оцінка впливу в динаміці виробничих чинників по санітарно-гігієнічним характеристикам умов праці часто є неможливою через часті та різноманітні перебудови виробництв, ліквідацію чи зміну форми власності, плинність кадрів тощо. Оцінка здоров'я досліджуваних когорт за результатами періодичних медичних оглядів і, особливо, за рівнем захворюваності з тимчасовою втратою працездатності [5][6] також є далекою від об'єктивної.…”
Section: вступunclassified
“…Occupational balance (OB) is one of the core concepts in occupational therapy (OT), and it has been found that quality of life can be improved by promoting it (Park et al, 2020). OB is related to quality of life, overall health and well-being, life satisfaction, and reduced stress levels (Håkansson et al, 2009; Håkansson and Ahlborg, 2016; Håkansson et al, 2020, 2021; Håkansson and Lexén, 2021; Wagman et al, 2019, 2020; Wagman and Håkansson, 2014a, 2014b; Wilcock et al, 1997; Yu et al, 2018). Even though the concept of OB was mentioned in Meyer’s articulation of the philosophy of occupational therapy (Meyer, 1977), standardized tools for measuring OB were not developed until much later.…”
Section: Introductionmentioning
confidence: 99%
“…The Occupational Balance Questionnaire (OBQ) and the revised OBQ11 have been widely used by researchers to measure OB ever since its development (Borgh et al, 2018; Gunal et al, 2021; Håkansson et al, 2019a, 2019b, 2021; Håkansson and Lexén, 2021; Kassberg et al, 2021; Magnusson et al, 2020; Wagman et al, 2016). The instrument, originally developed in Swedish, has been translated to a number of other languages (Gomez, 2017; Günal et al, 2020; Uhrmann et al, 2019; Yu et al, 2019), but not as yet to the Arabic language.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational balance (OB) refers to an individual’s self-perception of having the right amount and variety of occupations in his/her occupational pattern [ 1 ]. OB is related to a number of health indicators, such as quality of life [ 2–5 ], psychological wellbeing [ 6 ], perceived physical and mental health [ 7 , 8 ], sleep quality [ 9 ], reduced stress levels [ 8 , 10 , 11 ] life satisfaction [ 5 , 12 , 13 ], and family quality of life [ 14 ]. Measuring the level of OB and addressing OB issues among clients are important for occupational therapists working in rehabilitation settings [ 15 ].…”
Section: Introductionmentioning
confidence: 99%